Amino-functionalised β-diketiminate ligands (N-nacnacs): Synthesis and coordination chemistry with Main Group elements - Huan, D (2018)
This thesis examines the synthesis of a series of novel amino-functionalised β-diketiminate protio-ligands ("N-nacnacH"), and the subsequent application of these N-nacnac ligands in the coordination chemistry of Main Group elements, with the main focus being on the heavier Group 14 elements (Si, Ge, Sn). Comparison between the novel N-nacnac complexes and their classical β-diketiminate "Nacnac" analogues are drawn wherever possible, in order to highlight the differences in molecular properties brought about by the introduction of the σ-electron withdrawing/π-electron donating NMe2 functions at the ligand backbone. Chapter 3 introduces an optimised synthetic protocol for the preparation of N-nacnacH protio-ligands of the form (1-Ar)H (Ar = Ph, o-Xyl, Dipp). Attempts to synthesise (1-tBu)H and (1-Mes)H are frustrated by the formation of the rearranged products 2-tBu and 3, while modifying the work-up method eventually allows access to (1-tBu)H, albeit in low yield. The isolated protio-ligands (1-Ar)H exist in the diimine configuration in both solid- and solution-state, in contrast to the imino-enamine form typical of most NacnacH systems. Direct metallation of (1-Ar)H by nBuLi or AlMe3 generates the corresponding lithiated and aluminated complexes, respectively; the former are of synthetic significance as useful reagents for the synthesis of more exotic N-nacnac Main Group species via transmetallation. Spectroscopically, the donor capability of the NMe2 functions is demonstrated by 1H NMR resonances of the backbone γ-CH protons in the metallated compounds, which are shifted significantly upfield compared to their Nacnac counterparts. In chapter 4, the formation of N-nacnac-ligated monochlorotetrelenes of the generic form (1-Ar)ECl (E = Si, Ge, Sn) is discussed. The establishment of a library of germylenes and stannylenes bearing different N-bound aromatic substituents with varying degrees of steric bulk allows for a systematic study of the steric effects of the flanking aryl groups on the overall molecular metrics of these complexes. Most importantly, (1-Dipp)SiCl represents one of the first examples of a β-diketiminate-stabilised chlorosilylene. Preliminary reactivity studies have then been carried out with the bulky chlorotetrelene systems (1-Dipp)ECl (E = Si, Ge, Sn): chloride abstraction leads to the isolation of the corresponding cationic species [(1-Dipp)E][Al{OC(CF3)3}4]. Chapter 5 reports on further investigations into the reactivities of (1-Dipp)ECl (E = Ge, Sn). The syntheses and characterisation of the hydrido- ((1-Dipp)EH) and phosphaketenyl-tetrelenes ((1-Dipp)E(PCO)) via salt metathesis are reported, and the photochemistry of (1-Dipp)Ge(PCO) subsequently explored. UV-induced P─C bond cleavage generates the bicyclic germylene 4; the formation of which is proposed by DFT calculations to proceed via either a concerted mechanism (attack of the backbone C─C bond on phosphorus with accompanied loss of CO), or a step-wise pathway involving a germaphosphinidene intermediate. Chapter 6 presents the chemistry of the N-nacnac-stabilised chlorosilylene. Mild oxidation of (1-Dipp)SiCl affords the first example of a Lewis-acid-free sila-acyl chloride (1-Dipp)Si(O)Cl, which undergoes nucleophilic sila-acyl substitution to yield the sila-aldehyde (1-Dipp)Si[O(BEt3)]H and sila-ester (1-Dipp)Si(O)(OtBu). Notably, this substitution chemistry – while well known in carbonyl chemistry – is demonstrated for the first time to be compatible with heavier Group 14 carbonyl analogues. Crystallographic studies reveal very short Si=O bonds in the Lewis-acid-free siliconyl systems, which hint at marked multiple bond character of the Si=O function. On the other hand, metathesis reactions of (1-Dipp)SiCl with sources of H- or tBuO- are found to result in a ring contraction process, generating five-membered aza-butadienyl SiIV-complexes of the form (5-Dipp)Si(NDipp)R (R = H, tBuO). Intrigued by this mode of intramolecular rearrangement, and based on related examples with Nacnac-stabilised low-valent metal complexes, the relationship between the σ-donor capability of the R substituent and the tendency for compounds of the form (1-Dipp)SiR to undergo ring contraction has been probed, both experimentally and computationally. The proposed mechanism suggests that in most cases, strong σ-donating groups favour the N,C-chelate aza-butadienyl configuration under ambient conditions. This is broadly in line with the experimental findings, with the exception of the R = P(SiMe3)2 system which, together with the σ-withdrawing R = Cl system, exists in the N-nacnac-chelate form at room temperature.